Technological resources for second language pronunciation learning and teaching research-based approaches - McCrocklin, Shannon (Lexington Books, 2023)
"This book introduces research on a wide variety of technologies that can support second language pronunciation learning. While working to introduce practitioners to numerous technologies available, it also dives into the research-basis for their use, providing new studies and data featuring for language-learning contexts"--